Is readmission to hospital an indicator of poor process of care for patients with heart failure?. Issue 1 (2nd February 2004) - Luthi, J C; Burnand, B; McClellan, W M; Pitts, S R; Flanders, W D
Abstract : Background: Controversy exists about the appropriateness of using readmission as an indicator of the quality of care. A study was undertaken to measure the validity and predictive ability of readmission in this context. Methods: An evaluation study was performed in patients discharged alive with heart failure from three Swiss academic medical centres. Process quality indicators were derived from evidence based guidelines for the management and treatment of heart failure. Readmissions were calculated from hospital administrative data. The predictive ability of readmissions was evaluated using bivariate and multivariate analyses, and validity by calculating sensitivity, specificity, positive and negative predictive value, using process indicators as the "gold standard". Results: Of 1055 eligible patients discharged alive, 139 (13.2%) were readmitted within 30 days. The adjusted odds ratio (OR) for absence of measurement of left ventricular function was 0.70 (95% CI 0.45 to 1.08) for readmissions. In patients with left ventricular systolic dysfunction, three dose categories of angiotensin converting enzyme inhibitor were examined using ordinal logistic regression. The adjusted OR for these categories was 1.07 (95% CI 0.56 to 2.06) for readmissions. When using process indicators as the gold standard to assess the validity of readmissions, sensitivity ranged from 0.08 to 0.17 and specificity from 0.86 to 0.93. Conclusions: Readmission did not predict and was not a valid indicator of the quality of care for patients with heart failure admitted to three Swiss university hospitals.